Ruang sejahtera PPR Gombak Setia, Kuala Lumpur: cultivating topophilia through placemaking and community-oriented public space design - Zakariya, Khalilah; Nizarudin, Norhanis Diyana; Md Jani, Haza Hanurhaza; Tukiman, Izawati; Ab Sani, Jasasikin; Bahrudin, Fadzli Irwan; Sidek, Khairul Azami; Ruslan, Norbaiduri (Kulliyyah of Architecture and Environmental Design (KAED), IIUM, 2024)
Ruang Sejahtera is a communal space at PPR Gombak Setia, Kuala Lumpur activated by the IIUM project team in collaboration with Kelab Belia PPR Gombak Setia, with the support of other collaborating partners. This book documents the process and outcome of the project, through the theme of Cultivating Topophilia Through Placemaking and Community-Oriented Public Space Design. The process began by identifying the needs of the community, getting to know them and incorporating their input in the design process. The activation of the communal space was executed through a series of knowledge-transfer programmes, which contributed to the transformation of Ruang Sejahtera.